2020
DOI: 10.1126/sciadv.aax4690
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral delivery of CCL25 enhances immunotherapy against triple-negative breast cancer by recruiting CCR9 + T cells

Abstract: CCR9+ T cells have an increased potential to be activated and therefore may mediate strong antitumor responses. Here, we found, however, that CCL25, the only chemokine for CCR9+ cells, is not expressed in human or murine triple-negative breast cancers (TNBCs), raising a hypothesis that intratumoral delivery of CCL25 may enhance antitumor immunotherapy in TNBCs. We first determined whether this approach can enhance CD47-targeted immunotherapy using a tumor acidity–responsive nanoparticle delivery system (NP-siC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 66 publications
2
58
0
Order By: Relevance
“…There are no data on the influence of CCL25 on the recruitment of cells cooperating in the development of a tumor or its participation in angiogenesis [ 297 ]. However, this chemokine may cause infiltration of the tumor by cytotoxic TIL exhibiting CCR9 expression, which has an anticancer effect [ 298 ]. There are also indications that CCL25 causes lymphangiogenesis because activation of the CCL25→CCR9 axis increases the expression of VEGF-C and VEGF-D on the non-small-cell lung cancer cells [ 292 ].…”
Section: Ccr9 and Ccl25mentioning
confidence: 99%
“…There are no data on the influence of CCL25 on the recruitment of cells cooperating in the development of a tumor or its participation in angiogenesis [ 297 ]. However, this chemokine may cause infiltration of the tumor by cytotoxic TIL exhibiting CCR9 expression, which has an anticancer effect [ 298 ]. There are also indications that CCL25 causes lymphangiogenesis because activation of the CCL25→CCR9 axis increases the expression of VEGF-C and VEGF-D on the non-small-cell lung cancer cells [ 292 ].…”
Section: Ccr9 and Ccl25mentioning
confidence: 99%
“…CCR9/CCL25 also has an important role in tumor invasion and metastasis by promoting EMT in liver, non-small cell lung cancer, and breast cancer cell lines [ 36 , 37 ]. More interestingly, intratumoral delivery of CCL25 can enhance PD-L1/PD-1 antibody therapy against triple-negative breast cancer by recruiting CCR9+ T cells [ 38 ]. Regarding CCL28, recent studies have found that blocking of β-catenin–CCL28 can reduce Treg cell infiltration and inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Chen et al showed that the combined applications of NP-CCL25/ siCD47-induced immunotherapy and PD-L1/PD-1 blocker could synergistically enhance the anti-tumor effect. [33] Wang et al established a biochemical orthogonal system in which phenylalanine trifluoroborate (Phe-BF3) enters the cell as a tumor imaging probe and "cuts" the silyl ether, thereby removing the cell Silicon, so that the system can control the release of drugs in mice. When nanoparticles are combined with the design for delivery, Phe-BF3 catalyzed desalinization can release guest protein from the nanoparticle conjugate and selectively release the protein into tumor cells, thereby causing tumor regression and enhancing the anti-tumor immune response.…”
Section: Nano Drug Delivery Systemmentioning
confidence: 99%